A rare cause of acquired esotropia: Leprosy - Canleblebici, Mehmet; Yildirim, Hakan; Balbaba, Mehmet; Aydemir, Orhan (Wolters Kluwer Medknow Publications, 2022)
Leprosy is an infective chronic granulomatous disease involving the skin and peripheral nerves caused by Mycobacterium leprae. Complications such as lagophthalmos, corneal opacity and uveitis are common, but cranial nerve involvement is rarely seen. The fifth and seventh cranial nerves are most commonly involved. We report a case of acquired esotropia due to sixth nerve palsy following a rare cranial nerve involvement by leprosy.
Keywords: Acquired esotropia; lepromatous leprosy; nervus abducens paralysis; sixth cranial nerve palsy